Risk taking among high income individual taxpayers due to lack of tax evidence / Nurdiyana Osman - Osman, Nurdiyana (2013)
The purpose of this applied research is primarily to examine the extent of tax evasion among selected high income individuals seeking tax services from a tax agent and to investigate the motivation behind risk taking by selected high income individuals on tax evasion practices. This is because there are issues that on tax payers’ evasion arise nowadays. It is not only in Malaysia but it is happening around the world. Because of tax revenue forms a major component of the total revenue and its efficient collection is very important, thus tax evasion give huge implications to our nation nowadays. Hence, this research will try to identify the motivation that can facilitate to tax evasion among high income individual taxpayers. The researcher also attempted identify to what extent of individual taxpayer understands regarding tax evasion. The result of the analysis will then be presented in descriptive statistic and the results of the research show that there is some reasons to indicate tax evasion arises among high income individual taxpayers. The conclusion of this study shows that tax evasion give huge impact to government and also can effect to infrastructure facilities in Malaysia. The findings suggest that strengthen law enforcement and try to simplify tax requirements and tax system to ensure tax evasion can be reduces.